HARDNESS IMPROVEMENT OF HADFIELD STEEL AS FROG NOSE RAIL COMPONENT USING THERMOMECHANICAL TREATMENT METHOD - Giofan Ulinnuha, Yuma
Hadfield steel has superior mechanical properties, so it is often used in components that require resistance to impact loads and wear, such as frog noses. High hardness on the surface and toughness on the inside are the most critical requirements of the frog nose. The optimal hardness of frog nose, according to the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM.60 of 2012, is around 350 HB (370 HV). However, Hadfield steel in the as-cast condition has carbide deposits at the austenite grain boundaries, so it is brittle and has low toughness. Therefore, it is necessary to carry out a treatment to remove carbide at the austenite grain boundaries and increase the hardness according to the requirements of the frog nose component. The treatment carried out in this study was thermomechanical treatment with variations in pre-isothermal holding time (5 and 10 hours) and percent cold work (0, 10, 25, and 35%). The test results show that at each pre-isothermal holding time, the carbide phase is not continuous at the grain boundaries and is spread over the austenite matrix. Longer holding time causes less carbide fraction. In addition, the hardness value increases as the percentage of cold work increases. The cold work percentage of 10% resulted in the optimum hardness for the frog nose component for each variation of the pre-isothermal holding time, namely 363 ± 10,67 HV0,5 and 370,5 ± 15,33 HV0,5.